AEROBIC SPORULATING BACTERIA I. : Glucose Dehydrogenase of Bacillus cereus - Bach, John A. (1962)
Bach, John A. (Michigan State University, East Lansing) and H. L. Sadoff. Aerobic sporulating bacteria. I. Glucose dehydrogenase of Bacillus cereus. J. Bacteriol. 83:699–707. 1962.—A heat-resistant glucose dehydrogenase occurs in cultures of Bacillus cereus which are in the initial stages of sporulation. This enzyme is, kinetically, identical to the glucose dehydrogenase which can be extracted from mature spores, but is considerably more heat resistant than the spore-free enzyme. The two enzymes produce identity lines in two-dimensional immunodiffusion experiments, and their behavior in chromatographic and electrophoretic studies is also identical. A labile glucose dehydrogenase can be extracted from germinated spores of B. cereus. It differs from its stable counterparts in possessing a higher pH optimum for enzymatic activity.